2018
DOI: 10.1016/j.kontakt.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems as one of the factors in the development and persistence of homelessness

Abstract: The study aims to identify the presence of psychiatric disorders (and the different types) among the homeless, while also seeking a correlation between homelessness and mental health problems. The study was conducted as qualitative research at a low-threshold day treatment center in Trenčín between January 1 and October 1, 2017. The research sample consisted of twelve users of low-threshold social services, and through these participants we examined and identified not only the extent of psychiatric disorders p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…Individuals with schizophrenia or other psychotic disorders are highly likely to be marginalized by society but also by themselves. In addition, due to their condition, they can experience severe and long-term consequences such as unemployment, addiction, poverty, and homelessness (Evensen et al, 2016 ; Habánik, 2018 ; Ayano et al, 2019 ), which could explain why patients in the psychotic class are more likely to have risky network members. Moreover, our findings are in line with the study of Bogaerts et al ( 2020 ), which also found that psychotic symptoms can indeed diminish the patient's ability to complete essential daily tasks independently.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with schizophrenia or other psychotic disorders are highly likely to be marginalized by society but also by themselves. In addition, due to their condition, they can experience severe and long-term consequences such as unemployment, addiction, poverty, and homelessness (Evensen et al, 2016 ; Habánik, 2018 ; Ayano et al, 2019 ), which could explain why patients in the psychotic class are more likely to have risky network members. Moreover, our findings are in line with the study of Bogaerts et al ( 2020 ), which also found that psychotic symptoms can indeed diminish the patient's ability to complete essential daily tasks independently.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors contribute to such social and vital circumstances: domestic violence, unemployment, economic and family problems, childhood trauma, sexual assault, etc. (Habánik, 2018;Nishio et al, 2017). Among other factors, mental disorders play an important role, including psychotic disorders (Caton et al, 1994) and bipolar disorders (Maremmani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, as many as 100 million people were categorized as homeless, and over 1.6 billion individuals lacked adequate housing [1]. A wide range of multiple and interrelated factors contributes to homelessness such as domestic violence, social isolation, unemployment, addictions, mental illness, sexual assault, poverty, a critical shortage of affordable housing, financial difficulties, family breakdown, and adverse childhood experiences [26].…”
Section: Introductionmentioning
confidence: 99%